Ethical Evaluation and Action Research: Toward New North-South Research Collaborations? - Feagan, Mathieu (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2018)
This case study examines the author's experience gaining ethics approval for an action research project, to build capacity for new North-South research collaborations among graduate students trained in health and environment. It is argued that the ethics review process and action research framework seem to talk past each other. While the former may reinforce the divide between researchers and researched communities, potentially exacerbating North-South power asymmetries, the latter may presume that such asymmetries are overcome too easily through the good intentions of northern researchers, rather than through the work of southern actors to take back power. Considerations are offered for more realistic approaches to ethical North-South research collaborations.